Two-year outcomes after percutaneous coronary intervention of calcified lesions with drug-eluting stents - Généreux, Philippe; Redfors, Björn; Witzenbichler, Bernhard; Arsenault, Marie-Pier; Weisz, Giora; Stuckey, Thomas D.; Rinaldi, Michael J.; Neumann, Franz-Josef; Christopher Metzger, D.; Henry, Timothy D.; Cox, David A.; Duffy, Peter L.; et al. (International journal of cardiology, 2017)
Percutaneous coronary intervention (PCI) of lesions with coronary arterial calcification (CAC) is common and has been historically associated with an increased risk of adverse events. Whether the association between target lesion calcification (CAC) and outcomes differ across drug-eluting stent generation or between patients with high vs. low residual platelet reactivity (PR) remains unknown. We assessed the association of CAC with adverse ischemic and bleeding events among patients undergoing contemporary PCI with drug-eluting stents (DES). We included all 8582 patients who underwent successful PCI with DES in the prospective ADAPT-DES study. Patients were grouped according to whether or not they had CAC. We used a multivariable logistic regression analysis to determine independent predictors of CAC. We assessed the 2-year risk of major adverse cardiac events (MACE: Death, myocardial infarction, or stent thrombosis) and bleeding by constructing Kaplan-Meier curves and fitting unadjusted and adjusted Cox proportional hazards models. We assessed the influence of DES generation and PR on the effect of CAC on outcomes by including interaction terms in the models. CAC was present in 2644 (30.8%) patients. Age, smoking, hypertension, hyperlipidemia, insulin-treated diabetes, hemodialysis, and peripheral artery disease were independent predictors of CAC. Having a CAC was associated with increased unadjusted and adjusted hazards for 2-year MACE and bleeding. The association between CAC and ischemic outcomes was consistent across DES generations and PR (pinteraction>0.05). Contemporary DES PCI of calcified lesions is common and is associated with an increased risk of ischemic and bleeding complications.